The prevalence of dentin hypersensitivity among adult patients in Bangalore City - K F Imran Mohammed Khan; Nikhath Fathima; T L Ravishankar; Puneet Gupta (The journal of the Indian Association of Public Health Dentistry, 2013)
Objective: The aim of the study was to determine the Prevalence of Dentin Hypersensitivity (DH) among adult patients in Bangalore city, India and to suggest most appropriate clinical method to diagnose dentin hypersensitivity. Methodology: All adult patients attending the outpatient Department of the Oxford Dental College in Bangalore were considered for the study. Patients with sensitivity were subjected to detailed intra oral examination and interviewed using a structured questionnaire. All the teeth were tested for Evidence of dentin hypersensitivity by the use of air blast & water from the air-water jet syringe and by scratching the suspected tooth surfaces with a dental probe. The responses of each tooth ofthe subjects were recorded on the visual analog scale (VAS). Results: An overall prevalence of dentin hypersensitivity was 6.4%. About 86.8% patients perceived their experience of dentin hypersensitivity as sharp and 13.2% patients experienced it as dull, cold acted as the common stimulant. Premolars and molars were the most commonly affected teeth, maxillary arch have higher number of sensitive teeth compared to mandibular arch. DH was more elicited on the occlusal surface followed by cervical surfaces of the teeth. The perceived response of DH on VAS scale showed a significant difference among the methods (p<0.001) with probe method eliciting the highest response on the VAS scale followed by the air for 10 seconds. Conclusion: The prevalence of DH among adult population of Bangalore city was 6.4%. Probe was considered as most appropriate method to diagnose Dentin Hypersensitivity.